2007
DOI: 10.1016/j.bbamem.2006.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of poly(ethylene glycol) grafting density and polymer length on liposomes: Relating plasma circulation lifetimes to protein binding

Abstract: The incorporation of poly(ethylene glycol) (PEG)-conjugated lipids in lipid-based carriers substantially prolongs the circulation lifetime of liposomes. However, the mechanism(s) by which PEG-lipids achieve this have not been fully elucidated. It is believed that PEG-lipids mediate steric stabilization, ultimately reducing surface-surface interactions including the aggregation of liposomes and/or adsorption of plasma proteins. The purpose of the studies described here was to compare the effects of PEG-lipid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
197
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(215 citation statements)
references
References 51 publications
11
197
0
Order By: Relevance
“…On the other hand, the physicochemical characterization of bare NPs before exposure to body fluids remains crucial to reveal the correlations between the properties of NPs and PC composition (Figure 1). During the recent years, a large number of studies have been devoted to the characterization of NP-PC complexes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Furthermore, the scientific community is now moving from the The impact of nanoparticle protein corona on cytotoxicity, immunotoxicity and target drug delivery The bare NP (synthetic identity) that has a specific shape, size and charge is injected into the body.…”
mentioning
confidence: 99%
“…On the other hand, the physicochemical characterization of bare NPs before exposure to body fluids remains crucial to reveal the correlations between the properties of NPs and PC composition (Figure 1). During the recent years, a large number of studies have been devoted to the characterization of NP-PC complexes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Furthermore, the scientific community is now moving from the The impact of nanoparticle protein corona on cytotoxicity, immunotoxicity and target drug delivery The bare NP (synthetic identity) that has a specific shape, size and charge is injected into the body.…”
mentioning
confidence: 99%
“…Liposome-delivered anticancer agents, such as doxorubicin, have been proved to reduce side effects (cardiotoxicity, gastrointestinal toxicity, stomatitis, hair loss, etc) while exhibiting superior performance or preserving efficacy in clinical studies and maintaining an extended period of therapeutic concentration. [11][12][13] Considerable efforts have been devoted to extend the lifetime and integrity of liposomes in the bloodstream to periods on the order of days, raising the successful rate of transportation to the target location, 14,15 but the liposomes interfere with the passive drug release efficiency upon arriving at the destination and reduce clinical efficacy. [16][17][18][19] An active triggered mechanism is required to facilitate sufficient liposome content release in situ for optimal treatment effects, [16][17][18][19][20][21] and a non-invasive or minimally invasive monitoring method is required to adjust the topical release kinetics tailored for each subject in vivo by detecting drug-induced bio-events, with the goal of achieving and extending the therapeutic dosage period without exceeding toxic levels.…”
Section: Huang Et Almentioning
confidence: 99%
“…[8][9][10] This protective effect has been associated with the steric stabilization of liposomes that inhibits the uptake by MPS and prolongs the liposome circulation lifetime. 6,[8][9]11 The origin of this protection is still not fully understood but it has been proposed that the reduced binding of plasma proteins, including potential opsonizing factors, the limitation of direct interactions with cells of the reticuloendothelial system, and the inhibition of liposome-liposome aggregation could contribute to the reduced clearance of PEGylated liposomes [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…13,19 It was shown that improved circulation times of liposomes in the blood stream were obtained for liposomes with 2-10 mol% of interfacial PEG with a molecular weight between 350 and 2000 (anchored with distearoylphosphatidylethanolamine (DSPE) in these studies). 12,16 The protection of liposomes against phagocytosis was also improved with introducing PEG with a molecular weight of 2000 at its interface. 9 An increase of the PEG molecular weight to 5000 had no effect on half-life time of liposomes in the blood stream or, in some reports, slightly decreased it.…”
Section: Introductionmentioning
confidence: 99%